Influence of Distribution Modulus on the Compressive Strength of Ultra-High-Performance Concrete with Coarse Aggregate (UHPC-CA) - Zhihui Yu; Lishan Wu; Cong Zhang; Toshiyuki Bangi (Advances in Civil Engineering)
The Modified Andreasen and Andersen model (MAA model) is commonly chosen to realize condensed particle packing in ultra-high-performance concretes (UHPCs). In the MAA model, the q (distribution modulus) is a parameter that plays a critical role in the UHPC matrix design. The objective of this study is to figure out the influence of the q for the compressive strength of UHPC-containing coarse aggregate (UHPC-CA). Therefore, a series of investigations were conducted, covering the following aspects: first, the traditional design procedure, based on the MAA model, of UHPC-CA is revised by taking water and steel fibers into account in the particle packing system. The results show that the revised design process of UHPC-CA yielded more excellent products with better workability and compressive strength. Second, different q values which are 0.2, 0.21, 0.22, 0.23, and 0.25 are employed. The results show that when q is 0.25, the maximum compressive strength can be achieved. However, the flowability decreases with the increase of the q value. Third, an empirical calculation of the optimal coarse aggregate content in the light of different q values and maximum size of coarse aggregate are proposed.